The influence of financial technology and financial management knowledge on students' entrepreneurial interest at Bengkulu university - Andreansyah Ahmad Yusufi; Sri Adji Prabawa (Jurnal Mantik, 2024)
Difficulty finding employment is a problem that has not been resolved to date. Therefore, there is a need for awareness to create one's own jobs, so that the unemployment rate can be reduced. This research aims to determine the relationship between financial technology and financial management knowledge on the entrepreneurial interest of Bengkulu University students. This research uses quantitative methods with primary data. The population of this study were Bengkulu University students, and the sample used in this study was 190 samples. Data testing in this research used the help of SmartPLS software. The results of this research show that H1 is accepted, while H0 is rejected, indicating that financial technology (X1) and financial management knowledge (X2) influence students' entrepreneurial interest (Y). Furthermore, the results also show that financial technology (X1) and financial management knowledge (X2) contribute 66.8% to students' entrepreneurial interest (Y). the remaining 33.2% was influenced by other factors that were not examined in this study